Strategic negotiation in construction disputes: overcoming power imbalances and enhancing resolution through structured approaches - Sabri, Omar K. (Frontiers in Built Environment, 2025)
Construction disputes are prevalent because of the complexity of projects, heterogeneity of stakeholder interests, and contractual ambiguity. Although negotiation is still the preferred way to resolve these disputes, power inequalities, cognitive distortions, and adversarial behavior tend to undermine equitable and efficient solutions. This research analyzes strategic bargaining techniques by combining behavioral knowledge with formal bargaining models and alternative dispute resolution (ADR) models. It explores the influence of power relationships, psychological considerations, and interest-based negotiations on bargaining outcomes. It also looks at new technology like artificial intelligence (AI) and data-driven decision-making for their possible applications in improving negotiations. By using organized approaches, balance of negotiation leverage, and coordination, construction practitioners can maximize the effectiveness of dispute resolution and maintain long-term industry relationships. This research contributes to the development of improved models for negotiation that minimize conflicts and support sustainable project implementation.